Bureaucratic Corruptive Behavior: Causes And Motivation of State Civil Aparatures in Indonesia - Engkus (International Journal of Psychosocial Rehabilitation, 2020)
The main problem in this study is that the Corruption Perception Index (CPI) is still high. This is because the corrupt behavior and motivation of the state apparatus still occurs in Indonesia. The purpose of this study is to determine the causes and motivations of corruption that have occurred in the Bandung area. This study uses interviews and data collection from speakers. Researchers discovered that corrupt behavior is caused by behavior in the work environment, motivated by the greed of individuals or groups in the bureaucracy. The results of the study concluded that corrupt behavior led to accustomed and massive action, making this an extraordinary behavior with the involvement of the community, business and the bureaucracy itself. The researchers recommends that the treatment be consistent with the short and medium term plans and the long term patterns, all of which depend on the government as a policy maker in tackling corruption, naturally by relevant stakeholders, both the community , business, the involvement of bureaucracy itself, including the involvement of non-governmental organizations in the fight against corruption. and other related settings.